Temporal and spatial patterns of air temperature in a coastal city with a slope base setting. Issue 10 (19th May 2016) - Guan, Huade; Kumar, Vinodkumar; Clay, Roger; Kent, Christopher; Bennett, John; Ewenz, Caecilia; Hopkins, Graeme; Simmons, Craig T.
Abstract: In coastal cities with a slope base setting, effects of sea breeze and cold air drainage superpose on top of the urban heat island (UHI) effect. It is difficult to articulate the urbanization effect which, however, is important in developing summer heat mitigation solutions. The aim of this study is to address this challenge by investigating the temporal and spatial distribution of air temperature in the Adelaide metropolitan area of South Australia based on data from a monitoring network in 2011–2013. The results indicate that the dominant influence on the spatial variability of air temperature in winter is the urban heat island effect, followed by the prevailing nighttime northeasterly wind and cold air drainage. In summer, the dominant influence comes from daytime sea breezes, followed by the urban heat island effect, and the prevailing southeasterly nighttime wind. The urban heat island intensity is estimated based on various references where the influence of other factors is minimal. A clear nighttime urban heat island is observed over the Adelaide metropolitan area, with a mean intensity of 2.5°C for both summer and winter. The daytime urban heat island is not clear. On hot days, the city center develops a dominant nighttime urban heat island about 4°C warmer than the coast, stronger than an average summer night. Given multiple influences on the thermal climate in the Adelaide metropolitan area, it is suggested that the unique 500 m wide Adelaide parkland belt surrounding the city center be used as a reference to evaluate the Adelaide city center urban heat island in summer. A rural station, Edinburgh, can be used to evaluate the nighttime urban heat island intensity in the study area. Key Points: The Adelaide urban heat island is examined based on 3 year half‐hourly observation network data Regional winds and the UHI effects together shape the air temperature temporal and spatial patterns Daytime hotspots, warmer than CBD, occur in suburbs out of the reach of sea breezes